INSPIRASI AL-QURAN DALAM PEMBERANTASAN KORUPSI - Darlis Dawing (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
Corruption is an extraordinary crime. The impact is not only threatening the life order of society but also can tear the national stability. In 2017, Indonesia is still in the order of 90 of 176 countries in the world who have an index of achievement in eradicating corruption. This means that corruption in Indonesia is still very large. With this fact, this paper elaborates the concept of the Quran relating to corruption and its prevention. Through the study of thematic-integrative commentary with maqshidi analysis, it is found that the word as-suhtu, ghulul and al-fasad are terms that describe the phenomenon of corruption in Al-Qur`an. While preventing corruption, the Koran alleges the death penalty for perpetrators of crimes that damage both natural resources, human resources and community order.